The Participation of Women in the Greek Labour Force: A Spatial Analysis - Christina Kritikou; Michalis Agorastakis (European Regional Science Association (ERSA), 2006)
The participation of women in the labour market is being effected by their biological circle and by social standards and stereotypes that delineate domestic work as woman's primary activity. Particularly in Greece, the sovereignty of Mediterranean family model undermines the effectiveness of policies aiming to promote feminine employment and thus, constitutes a brake for labour equality between the sexes. Consequently, female employment rate continues to remain in the lowest levels among E.U. countries, despite the fact that several issues have been raised during the past years, such as: the evolution of the legislative system towards equality, higher educational level of women, increased consuming needs, the decrease of fertility, the struggle of women for economic independence etc. Nevertheless, the participation of Greek women in the labour market continues to be 8-10 percent below the average of E.U. countries. In this paper, we try to identify and represent the participation of women in the work force, in terms of employment and unemployment, while emphasizing to the spatial and age-structured patterns in national level. The data used in this analysis, emanate from the latter Population Census of 2001, conducted by the National Statistical Service of Greece (ESYE). The spatial level of reference is the Municipality administrative level, which allows us to identify the "unfavorable" regions of Greece, with increased unemployment and low participation in the economically active population, forming clusters with similar characteristics in the employment sector. Using statistical methods of multivariate analysis, we examine employment indices of economically active and inactive women, employed and unemployed women, as well as the distribution of employment according to the three sectors, focusing on age-related groups, responsible for the intensity of the phenomenon. In-depth spatial and age-related analysis of feminine employment reveals the intense problem of mountainous and rural regions, while the age distribution concerning unemployment is identified. Finally, we are able to draw coherent conclusions for the degree of convergence/divergence between administrative units in Greece and also with the E.U. average.
Keywords: 330